Churches in Poland Facing the German Occupation 1939–1945 - Kiec, Olgierd (Poznańskie Studia Slawistyczne, 2016)
Poland and Polish nationalism are widely identified with Catholicism. However, the population of the Polish state was not homogenous ethnically and religiously – in 1921 the number of ethnic/confessional minorities reached the high level of over 30 percent. The Second World War was a fundamental change in Polish history – the new people’s republic, formed after 1945, has been a totally different state from the Second Republic of Poland, which existed 1918–1939. Unfortunately, very little is known about the impact of Churches (Catholic, Protestant, Orthodox) in shaping the Polish, Ukrainian, Belorussian and German nationalisms during the wartime as well as the attitudes of clergymen towards the German occupants.